American beauty - Ball, Alan; Mendes, Sam; Cohen, bruce; Jinks, Dan; Bening, Annette; Spacey, Kevin; Dreamworks Pictures ([Universal City, CA] : Dreamworks Home Entertainment, 2000)
When midlife crisis hits, Lester Burnham's fascination with a young girl spurs him to make some major changes in his life
Winner of 5 Academy Awards (1999): Best Picture, Best Actor (Kevin Spacey), Best Director, Best Original Screenplay, and Best Cinematography
Also available in VCD Format
Title from title screen
Photography, Conrad L. Hall; editors, Tariq Anwar and Chris Greenbury; music, Thomas Newman
Cast: Annette Bening, Kevin Spacey, Wes Bentley, Thora Birch, Chris Cooper, Peter Gallagher, Allison Janney, Mena Suvari
Keywords: Suburban life -- United States -- Drama; Midlife crisis -- Drama; Feature films